2020
DOI: 10.1021/acs.energyfuels.9b03689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Rejuvenators on the Chemical, Thermal, and Rheological Properties of Asphalt Binders

Abstract: Rejuvenators are used to restore the properties of reclaimed asphalt pavement (RAP) binders through readjusting the balance between the asphaltene and maltene fractions. To properly understand the effect of rejuvenators, it is important to analyze the chemical changes in the rejuvenated binders and to relate these changes to the rheological properties of the binders. In this study, RAP binders were blended with a bio-based and an aromatic extract petroleum-based rejuvenator additive. Chemical and thermal techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 34 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…29 Bio-oils can also be used as rejuvenators. 30 Rejuvenators based on algae, animal waste, or vegetable oil are usually in liquid form, and their introduction to aged asphalt could help revitalize aged asphalt. Bio-oil from oak wood is a bitumen replacer with properties similar to those of bitumen; bio-oil from oak wood can be modified by polymers or rubber, and it is resistant to thermal cracking.…”
Section: Composition Of Bio-oilsmentioning
confidence: 99%
“…29 Bio-oils can also be used as rejuvenators. 30 Rejuvenators based on algae, animal waste, or vegetable oil are usually in liquid form, and their introduction to aged asphalt could help revitalize aged asphalt. Bio-oil from oak wood is a bitumen replacer with properties similar to those of bitumen; bio-oil from oak wood can be modified by polymers or rubber, and it is resistant to thermal cracking.…”
Section: Composition Of Bio-oilsmentioning
confidence: 99%
“…Mullapudi et al [20] mixed different proportions of extracted RAP binders with VABs, and it was found that the oxygenated functional groups' indices-ISO and ICO-increased with increasing RAP binders' percentages. The binder in the RAP contained a high asphaltene fraction [21], thus EABs' maltenes and asphaltenes fractions change based on the interactions between the RAP binder and VAB. The TGA is utilized to examine changes in the components of asphalt binders by monitoring changes in thermograph (TG) parameters: the onset temperature (Tonset), endset temperature (Tendset), and residue's percentage.…”
Section: Introductionmentioning
confidence: 99%
“…Asphaltene has one peak in the DTG; however, maltene presents two peaks [11]. Thus, the disappearance of the second region in the DTG indicates a decrease in the maltene component of the EABs The RAP binder has a high fraction of asphaltene [19], and thus the fractions of EABs-maltenes and asphaltenes-change based on the interactions between the RAP binder and VAB. These interactions and related changes in asphalt fractions can be explored through TGA.…”
Section: Introductionmentioning
confidence: 99%